2005
DOI: 10.5194/acp-5-2635-2005
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of OH variability as inferred by an inversion of atmospheric transport and chemistry of methyl chloroform

Abstract: Abstract.We developed an iterative inverse method to infer inter-annual sources and sinks of methyl chloroform (MCF) from atmospheric measurements, on a monthly basis. The methodology is presented and used to estimate two decades of OH variability between 1980 and 2000, using varying meteorology. When OH concentrations are adjusted with loose prior errors and MCF emissions are adjusted within inventory bounds, we show that substantial OH inter-annual variability (8.5±1.0% of the mean) and trend (−0.7%.yr −1 ) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
206
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(235 citation statements)
references
References 38 publications
27
206
2
Order By: Relevance
“…In this study, the errors are set to ±100% of the maximum flux in the grid cell over the inversion period for H 2 , ±1% of the flux for MCF (in order to constrain OH), CO, CH 4 and HCHO. The error of ±10% for OH concentrations is consistent with the differences between estimates of the OH concentrations of several studies (Krol et al, 2003;Prinn et al, 2005;Bousquet et al, 2005). Finally, the error on the initial concentrations of HCHO, MCF and H 2 is set at ±10%.…”
Section: General Settings Of Pyvar/lmdz-sacssupporting
confidence: 62%
See 2 more Smart Citations
“…In this study, the errors are set to ±100% of the maximum flux in the grid cell over the inversion period for H 2 , ±1% of the flux for MCF (in order to constrain OH), CO, CH 4 and HCHO. The error of ±10% for OH concentrations is consistent with the differences between estimates of the OH concentrations of several studies (Krol et al, 2003;Prinn et al, 2005;Bousquet et al, 2005). Finally, the error on the initial concentrations of HCHO, MCF and H 2 is set at ±10%.…”
Section: General Settings Of Pyvar/lmdz-sacssupporting
confidence: 62%
“…Its concentration is estimated in the model in an indirect way: using methyl chloroform (CH 3 CCl 3 or MCF) which reacts only with OH and the sources of which are quantified with acceptable accuracy (Krol et al, 2003;Prinn et al, 2005;Bousquet et al, 2005). The adequacy of SACS with the chemistry model INCA (Interactive Chemistry and Aerosols) (Folberth et al, 2005) is evaluated in Pison et al (2009).…”
Section: General Settings Of Pyvar/lmdz-sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Montzka et al (2011) inferred small interannual OH variability and trends (typical OH changes from year to year of less than 3 %) and attributed previously estimated large year-to-year OH variations before 1998 (e.g. Bousquet et al, 2005;Prinn et al, 2001) to overly large sensitivity of OH concentrations inferred from methyl chloroform measurements to uncertainties in the latter's emissions. However, Prinn et al (2005) also showed lower post-1998 OH variability that they attributed to the lack of strong post-1998 El Niño events.…”
Section: Oh Oxidationmentioning
confidence: 99%
“…The role of the OH sink 3690 P. Bousquet et al: Source attribution of the changes in atmospheric methane for [2006][2007][2008] in atmospheric CH 4 variations may be significant Prinn et al, 2005;Rigby et al, 2008) but it is still controversial, given discrepancies in the magnitude of OH interannual variations computed by atmospheric chemistry models (∼1-3%, (Dentener et al, 2003;van Weele et al, 2009) or estimated by atmospheric inversions based on 1,1,1-trichloroethane (∼4-10%, Bousquet et al, 2005;Krol and Lelieveld, 2003;Prinn et al, 2001).…”
Section: Introductionmentioning
confidence: 99%